Pd/Ti electrocatalyst in technological significance reactions - Aguirre, María del Carmen (2015)
New materials operating as future electrocatalysts into fuel cells or in environmental remediation processes are continuously under research. Here we studied palladium modified electrodes, such as Pd/Ti and Pd/GC (glassy carbon), which are electrochemically built and used in chromate detection, in oxygen reduction and alcohols oxidation reaction. The palladium material electrodeposited at constant potential was characterized by X-ray diffraction, and scanning electron microscopy. The response of Pd/Ti nanoelectrodes, by oxygen reduction was observed in alkaline and acid supporting electrolytes. The diffusion coefficient of 2 10-5 cm2/s with a transference of 4e -in 0.1M H2SO4 solution was calculated. A higher coefficient value in 0.05 M NaOH was evaluated, because Ti substrate is also active in oxygen reduction in alkaline media. The reduction of Cr(VI) with Pd/Ti electrode proceeds at +0.58 V vs Ag/AgCl in H2SO4 0.1M, with a diffusion coefficient of 2.210-5 0.01 cm2/s and a linear range between 0.019 -0.69 mM Cr(VI). The lowest sensitivity 0.5 M Cr(VI) was determined with Pd/Ti electrode in the range permissible by drinking water of The oxidation of alcohol molecules in alkaline environment showed by Tafel curves, the activity order on Pd/Ti electrocatalyts is ethanoln-propanol >ethylene glycol. The calibration curve obtained by anodic peak current density of cyclic voltammetries upon an increasing alcohol concentration (3 to 90 mM alcohol) in NaOH 0.05 M, permitted to evaluate an activity of PdTi(+0.1V)PdTi(-0.3V)>PdTi(-0.9V). The performance of Pd/Ti electrocatalysts was better when compared with a modified Pd/GC electrocatalyst, in the studied reactions.